The Sleep That Changed Everything - Brown, Lee Ann (Book collections on Project MUSE., 2003)
LEE ANN BROWN is Assistant Professor of English at St. John's University in New York City. A poet and filmmaker whose first book, Polyverse (1999), won the New American Poetry Series Award, she is also the founder and editor of the small press Tender Buttons.